2008
DOI: 10.7326/0003-4819-148-5-200803040-00003
|View full text |Cite|
|
Sign up to set email alerts
|

Improved Diagnostic Evaluation of Suspected Tuberculosis

Abstract: The ELISpot(PLUS) assay is more sensitive than standard ELISpot and, when used in combination with tuberculin skin testing, enables rapid exclusion of active infection in patients with moderate to high pretest probability of tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
119
1
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(128 citation statements)
references
References 48 publications
3
119
1
5
Order By: Relevance
“…Consequently, novel concepts have been investigated that include the use of different epitopes of RD antigens [11,12,36,37,58], readout different from IFN-c such as chemokines or cytokines [56,58], new antigens different from the RD genomic region, such as those defined as Rv1733c, Rv2029c, Rv2032, Rv2626c, Rv2627c, Rv2628 and HspX [29,[59][60][61], additional cytokines [56] or characteristic phenotypic markers [11,12,36,62]. Diagnostic sensitivity of IGRA can also be enhanced by incorporation of a novel RD1-encoded antigen, Rv3879c, without compromising diagnostic specificity [63]. Moreover, as active tuberculosis involves recruitment of antigen-specific T-cells to the site of the active infection, the comparative analysis of antigenspecific cells from the blood and the site of disease (e.g.…”
Section: Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, novel concepts have been investigated that include the use of different epitopes of RD antigens [11,12,36,37,58], readout different from IFN-c such as chemokines or cytokines [56,58], new antigens different from the RD genomic region, such as those defined as Rv1733c, Rv2029c, Rv2032, Rv2626c, Rv2627c, Rv2628 and HspX [29,[59][60][61], additional cytokines [56] or characteristic phenotypic markers [11,12,36,62]. Diagnostic sensitivity of IGRA can also be enhanced by incorporation of a novel RD1-encoded antigen, Rv3879c, without compromising diagnostic specificity [63]. Moreover, as active tuberculosis involves recruitment of antigen-specific T-cells to the site of the active infection, the comparative analysis of antigenspecific cells from the blood and the site of disease (e.g.…”
Section: Sectionmentioning
confidence: 99%
“…The positive predictive value for the development of tuberculosis will most likely be higher with an IGRA than with the tuberculin skin test because of the higher test specificity and similar, or probably higher, sensitivity. In immunocompetent individuals, the negative predictive value of IGRA for active tuberculosis is very high, if combined with a negative result of the tuberculin skin test [63,104]. In immunocompromised individuals the negative predictive value of IGRA needs to be established.…”
Section: Sectionmentioning
confidence: 99%
“…These immunoassays detect in vitro interferon-c secreted by peripheral blood mononuclear cells in response to specific antigens of M. Tuberculosis. Currently, multiple data show that IGRA tests are equally sensitive but more specific than TST in diagnosing latent tuberculosis infection and active tuberculosis [35,36]. This seems true both in immunocompetent and immunocompromised patients [36,37].…”
Section: Tuberculin Skin Test (Tst) and Interferon Gamma Release Assamentioning
confidence: 99%
“…[98][99][100] Ferrara et al 79 found high rate of undetermined results Other studies have shown that the prevalence of positive ELISPOT results was higher than that found using the TST, mainly in immunosuppressed patients. 16,102,103 79 suggested that IGRAs specificity is higher than TST specificity for the diagnosis of tuberculosis infection.…”
Section: Elispot (Available In the Market As T-spottb ® Oxfordmentioning
confidence: 99%
“…It has been approved for use in Europe, as well as by the FDA. 11,[15][16][17] These assays have good sensitivity and specificity for the diagnosis of TB, presenting advantages in comparison with the TST, mainly in patients with some degree of immunosuppression. [18][19][20][21] Early diagnosis and treatment of tuberculosis infection, avoiding progression to disease, are challenges that need to be overcome so that worldwide control of TB can be achieved.…”
Section: Introductionmentioning
confidence: 99%